Aplicação de ultrassom para remoção de enxofre e de nitrogênio do óleo diesel: avaliação de parâmetros do processo e determinação de enxofre e de nitrogênio por técnicas espectrométricas e cromatográficas - Mello, Paola de Azevedo (2011)
In the present work, the ultrasound assisted oxidation of sulfur and nitrogen compounds present in diesel fuel was investigated. The oxidized compounds are more polar than their original forms and can be removed from oil by liquid-liquid extraction. Initially, different methods for the determination of total sulfur and nitrogen concentration were evaluated for the knowledge of sample composition before and after the treatment. For sulfur it was investigated the determination by ultraviolet fluorescence by means of direct injection in the total analyzer and also by inductively coupled plasma optical emission spectrometry (ICP OES) after sample decomposition by microwave assisted wet digestion in closed vessels. For nitrogen, the determination was performed by chemiluminescence after direct injection using the total analyzer. Moreover, chromatographic parameters were optimized for analysis of sulfur compounds by gas chromatography with pulsed flame photometric detector (GC-PFPD). Regarding to the removal process, different ultrasound systems were evaluated with different frequencies and nominal powers, among them ultrasonic baths (35 kHz and 160 W, 35 kHz and 200 W, 130 kHz and 200 W and 582 kHz e 200 W), ultrasonic horns (20 kHz and 130 W and 20 kHz and 750 W) and also a cup horn system (20 kHz and 750 W). For all systems, two oxidation mixtures were evaluated: the combination H2O2/H3PO4.12WO3 with tetraoctylammonium bromide as surfactant and also the combination H2O2/AcOH. In addition, the removal efficiency under mechanical agitation (2000 rpm) was also investigated instead of using ultrasound. Better results were obtained for lower frequencies and higher power, by using immersion probes and with the H2O2/AcOH oxidation mixture. After choosing the suitable system, process parameters were evaluated in order to obtain better efficiency, such as: reaction temperature, time of ultrasound or mechanical agitation, solvent for extraction and its amount, the amount of AcOH and H2O2, the type of the carboxylic acid, the ultrasound amplitude, the addition of gases to the reactor, the addition of auxiliary reagents to the oxidation mixture and the use of a previous solvent extraction before the oxidative process. After process parameters optimization the diesel oil samples, with different initial sulfur and nitrogen concentrations and different classes of sulfur compounds were submitted to the oxidative process, with and without ultrasound. Using 7 min of ultrasound (20 kHz, 750 W, amplitude of 40%) at 90 °C, for the treatment of 25 mL of diesel oil, using molar proportion of S+N:H2O2:AcOH corresponding to 1:28:557 and extraction with MeOH (3x8 mL) the removal efficiency was from 80 to 86% for sulfur and from 74 to 91% for nitrogen. Without ultrasound under the same experimental conditions, the sulfur and nitrogen removal efficiency were from 50 to 75% and 75 to 90%, respectively, indicating the improvement of the ultrasound energy on the sulfur removal efficiency.